The Development, Coupling Degree, and Value-Added Capability of the Digital Economy and Manufacturing Industry in China - Rengang Su; Yinhai Fang; Xianglian Zhao (Systems, 2023)
Our goal in this study was to measure the developments, coupling degrees, and value-added abilities of the digital economy and manufacturing industry in China. We clarified the relationship between the coupling degree and value-added ability of the system. We also identified the dynamic factors that affect the value-added ability of the system. On the basis of a literature review and theoretical analysis, we constructed a vector coupling model of the evolution of the system, and we used a combination of entropy weight, SFA, and other methods. We found that the development levels of the digital economy and manufacturing industry in China have continued to im-prove, but we noted considerable differences between different provinces. Furthermore, by using model decomposition, we calculated the average contribution rate of the digital economy, manufacturing industry, and the coupling degree of the two systems to the added value of the overall system. The digital economy has rapidly developed in all provinces and has played a notable role in promoting the value-added capacity of the system, especially in provinces that were lagging. This catch-up effect of the digital economy can narrow the economic gap between provinces. The digital economy is highly efficient, enabling, and inclusive, and thus can be coupled with the development of the manufacturing industry to produce synergies and enhance the value-added abilities of the two systems.